The meanings of the symbol in wall ceramics and its representations in the products of students of the Department of Art Education (Al-Academy, 2025)
The goal of this research is to reveal the aesthetic characteristics of wall ceramic art in students’ works. To achieve the goal of the research, the researcher prepared a research tool consisting of paragraphs to measure what she found to measure, after it was approved by a group of arbitrators within the art education specialty, and it was applied to bachelor’s students in the Department of Education. Technical for the academic year (2022-2023). In light of the tool, the researcher reached a number of results and conclusions, the most prominent of which are:1. Some types of shapes in wall ceramic work have a pictorial approach in their formal and color relationships, and this is embodied in the students’ works and this appears in sample (1-2)2. The artistic and aesthetic characteristics emphasized the student’s interest in space, texture, color, movement, and the direction of lines to confirm the dominance of artistic elements as in the samples (1-2-3).3. Contemporary wall ceramics gave a circulation context through its intertwining in Iraqi architecture and giving a diverse rhythm to the wall.